CDP571, a humanised monoclonal antibody to tumour necrosis factor α, for moderate to severe Crohn's disease: a randomised, double blind, placebo controlled trial. Issue 10 (10th September 2004) - Sandborn, W J; Feagan, B G; Radford-Smith, G; Kovacs, A; Enns, R; Innes, A; Patel, J
Abstract : Background: Targeting tumour necrosis factor α (TNF-α) has demonstrated efficacy in Crohn's disease. Aim: To evaluate CDP571, a humanised antibody to TNF-α, for treating active Crohn's disease. Patients: A total of 396 patients with moderate to severe Crohn's disease. Methods: In a 28 week, randomised, double blind, placebo controlled trial, patients received intravenous CDP571 (10 mg/kg) or placebo every eight weeks to week 24. The primary outcome measure was clinical response (a decrease in the Crohn's disease activity index (CDAI) to ⩾100 points or remission (CDAI score ⩽150 points)) at week 28. A secondary outcome measure was clinical response (using the same definition) at week 2. Results: Clinical response occurred at week 28 in 80/263 (30.4%) CDP571 patients and 31/132 (23.5%) placebo patients (p = 0.102). Clinical response at week 2 occurred in 90/263 (34.2%) CDP571 patients and 28/132 (21.2%) placebo patients (p = 0.011). Post hoc exploratory subgroup analysis of 159 patients with baseline C reactive protein (CRP) ⩾10 mg/l demonstrated significant differences between CDP571 and placebo in clinical response rates at weeks 2 (CDP571, 50/101 (49.5%); placebo, 9/58 (15.5%); p<0.001) and 28 (CDP571, 29/101 (28.7%); placebo, 7/58 (12.1%); p = 0.018). Adverse events occurred at similar frequencies in both treatment groups. Conclusions: CDP571 is modestly effective for short but not long term treatment of unselected patients with moderate to severe Crohn's disease. The clinical relevance of this short term effect is unclear. Post hoc analysis suggests both short and long term efficacy of CDP571 in patients with elevated baseline CRP (⩾10 mg/l). CDP571 is well tolerated.